Sound event aware environmental sound segmentation with Mask U-Net. (17th October 2020) - Sudo, Y.; Itoyama, K.; Nishida, K.; Nakadai, K.
Abstract : This paper proposes an environmental sound segmentation method using Mask U-Net. In recent years, human–robot interactions, especially speech dialogue, have been assessed by auditory scene analysis. Methods, such as noise reduction, section detection, and sound source separation have been proposed for robot audition, acoustic signal processing, and machine learning. However, such conventional approaches have three drawbacks: (1) Many studies have analyzed individual functions, which are regarded as being a cascade. Cascade systems can, however, result in the accumulation of errors generated at each functional block. (2) Unlike conventional cascade systems, deep learning-based methods that simultaneously detect sections, separate sound sources, and identify classes have also been proposed for speech separation. These techniques can be extended for multiple classes of environmental sounds, but their performance becomes degraded with large variations in sound event lengths among classes. (3) In addition, these methods have recurrent neural network layers making it difficult to process calculations in parallel. This paper proposes an environmental sound segmentation method called Mask U-Net, which robustly differentiates sound event lengths among classes. Simulation experiments using a developed 75-class environmental sound data set showed that the proposed method was faster than conventional methods and showed high segmentation performance. GRAPHICAL ABSTRACT: UF0001